The degree of using electronic information sources in scientific research from the point of view of graduate students in the Faculty of Education at Tishreen University - طرفه هبه (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to identify the reality of the use of electronic information sources in scientific research by graduate students and the effect of variables (gender, computer training courses, place of residence) on that. In order to achieve the objectives of the research, the descriptive approach was used by designing a questionnaire consisting of (21) statements distributed on two axes, and the research sample consisted of (74) graduate students in the Faculty of Education at Tishreen University, and among the most prominent results of the research were: - The degree of using electronic information sources in scientific research came by graduate students in the Faculty of Education at Tishreen University. The dissertations and scientific research available on the Internet were in pdf format, and the local refereed magazine sites were among the most used electronic information sources in scientific research by graduate students in the Faculty of Education at Tishreen University. - The fields of (choosing a topic for research, determining its problem and goals, and reviewing previous studies) came first in terms of relying on electronic information sources. - There were no statistically significant differences between the opinions of graduate students regarding the reality of using electronic information sources in scientific research according to the variables of sex and housing. As for the variable of training courses on the use of computers and the Internet, statistically significant differences were found in favor of students who followed one or more training periodicals.